EVALUATION OF LEARNING PROGRAMS WITH THE CIPP MODEL IN COLLEGE A THEORETICAL REVIEW - Endang Suparman; Karja Sangadji (International Journal of Education, Information Technology, and Others, 2020)
Evaluation as a process of determining at what level educational goals are actually realized. Program evaluation is an "effort to find out the level of implementation of a policy carefully by knowing the effectiveness of each component. Abbreviations of the concept of evaluation of the CIPP model (Context, Input, Process, and Product) The concept of the CIPP Stufflebeam model with the view that the important purpose of evaluation is not prove but to improve. The CIPP concept is as follows: context evaluation is intended to assess the situation that is being carried out by an educational institution. Input evaluation is to give consideration to the success of the curriculum. Process evaluation is about implementing an innovation curriculum. Evaluation of the results of the main objective is to determine the extent to which the learning program implemented has been able to meet the needs of groups who use it. The fourth evaluation is a series of wholeness. Evaluation of learning programs using the CIPP model developed and implemented by lecturers in tertiary institutions should reach an assessment of: (1) learning designs that include competencies developed, selected learning strategies, and program content, (2) implementation of learning programs or quality of learning, and (3) learning program results